Electron beam radiation induced GMA-grafted cotton fibers optimized with phosphoric acid for adsorption of metformin hydrochloride from aqueous solution - Alnaisani, Mohammed S.; Abdullah, Luqman Chuah; Ting, Teo Ming; Md Jamil, Siti Nurul Ain; Zainuddin, Halimatun Sakdiah; Abdullah, Mohammed; M. Saber, Shihab Ezzuldin (North Carolina State University, 2026)
Using an electron beam (EB) accelerator, natural cotton fibers were pre-irradiated for grafting with glycidyl methacrylate (GMA). Subsequently, phosphoric acid (phosphoric) was used to functionalize the GMA-grafted fibers (cotton-g-GMA). Various analyses, including scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), thermogravimetric and derivative thermogravimetric (TG-DTG) analysis, and surface charge analysis, were performed to evaluate the morphological and physiochemical attributes of the fibrous adsorbent. The prepared adsorbent was then tested for metformin hydrochloride (MFH) adsorption from an aqueous solution. The MFH’s adsorption on phosphoric-cotton-g-GMA followed a pseudo-2ndorder model. The Langmuir isotherm model was close behind the Redlich-Peterson model, which described the equilibrium data the best, according to the isotherm analysis. At 24.7 mg/g, the maximum adsorption capacity was attained. Meanwhile, the regeneration and recycling of the adsorbent were possible for at least five cycles, with recovery of MFH being nearly 94.65% in the final cycle. According to the findings, it was deduced that the fibrous phosphoric-cotton-g-GMA adsorbent could be used to successfully eliminate MFH at an industrial scale.